Genomic analysis of two novel bacteriophages infecting Acinetobacter beijerinckii and halotolerans species - Gomes, Marta Teresa Silva (2023)
Bacteriophages are the most diverse genetic entities on Earth. In this study, two novel bacteriophages, nACB1 (Podoviridae morphotype) and nACB2 (Myoviridae morphotype), which infect Acinetobacter beijerinckii and Acinetobacter halotolerans, respectively, were isolated from sewage samples. The genome sequences of nACB1 and nACB2 revealed that their genome sizes were 80,310 bp and 136,560 bp, respectively. Comparative analysis showed that both genomes are novel members of the Schitoviridae and the Ackermannviridae families, sharing ≤ 40% overall nucleotide identities with any other phages. Interestingly, among other genetic features, nACB1 encoded a very large RNA polymerase, while nACB2 displayed three putative depolymerases (two capsular depolymerases and one capsular esterase) encoded in tandem. This is the first report of phages infecting A. halotolerans and beijerinckii human pathogenic species. The findings regarding these two phages will allow us to further explore phage—Acinetobacter interactions and the genetic evolution for this group of phages.